2019
DOI: 10.1080/10291954.2019.1662210
|View full text |Cite
|
Sign up to set email alerts
|

Minimum corporate website disclosure levels and information asymmetry: Evidence from Johannesburg Stock Exchange small-cap companies

Abstract: The use of corporate websites as communication medium may contribute to good governance and specifically transparency as one of the basic principles of governance, mitigating the effect of the agency problem. The primary objective of this study was to ascertain the link between voluntary corporate website disclosure and information asymmetry for the smallest JSE-listed companies. Rule 26, as issued by the LSE for its AIM-listed companies, was used as proxy for disclosure while the bid-ask spread stood as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Some of these studies have found an empirical evidence of a negative relationship between web-based disclosure and information asymmetry, however, this association was not significant. This is the case of the study of Nel and Baard (2019) conducted in South Africa. The study postulated that the disclosure of information on the company’s web site may not be sufficient in persuading investor to change their trading behavior.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some of these studies have found an empirical evidence of a negative relationship between web-based disclosure and information asymmetry, however, this association was not significant. This is the case of the study of Nel and Baard (2019) conducted in South Africa. The study postulated that the disclosure of information on the company’s web site may not be sufficient in persuading investor to change their trading behavior.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Web-disclosure is important for good corporate governance as the practice promotes corporate transparency and accountability which in turn increases investor confidence (Nel & Baard, 2019;Sandhu & Singh, 2019). There is therefore a call for improvement in quality web-disclosure as it offers companies advantages which cannot be realised through traditional print-based disclosure practices (López-Arceiz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Boubaker et al, 2012;AbuGhazaleh et al, 2012;Basuony & Mohamed, 2014;Sushila & Amol, 2016;Omran & Ramdhony, 2016;Qasim & Al Barghouthi, 2017;Adityawarman & Khudri, 2017;Aboutera & Hussein, 2017;Ahmed et al, 2017 ;Qasim & Al Barghouthi, 2017;Mokhtar,2017;De Silva & Ajward, 2018;Abdi et al, 2018;Hussain, 2018;Sarifudeen, 2021;Khlifi, 2021 Mokhtar (2017) . ‫مثل؛‬ ‫اسات‬ ‫الدر‬ ‫بعض‬ ‫لجأت‬ ‫فقد‬ (Debreceny et al, 2002;Xiao et al, 2004;AbuGhazaleh et al, 2012 (Debreceny, et al, 2001;SEC,2008;Cormier et al, 2009;bahl & lal., 2012;Nel & Baard, 2019;Mendes-Da-Silva & Onusic, 2014;Singh, 2013;Omran & Ramdhony, 2016;Hashim et al,2014;Garg & Gakhar, 2010;Boubaker et al,2012;De Silva & Ajward, 2018;، Samaha & Abdallah, 2012;Aly et al,2010;Ahmed et al, 2017;Mokhtar, 2017;Yassin, 2017;Hassan et al, 2022;Hussein & Nounou, 2021;Desoky, 2009;…”
Section: ‫دفعت‬ ‫كما‬mentioning
confidence: 99%
“…;Abdi et al, 2018;Henchiri, 2011;Mohamed & Basuony, 2015;Roberts et al, 2012;qasim & al barghouthi, 2017;Aboutera & Hussein, 2017). (Khalil & Maghraby, 2017 ;Mokhtar, 2017;De Silva & Ajward , 2018;Abdi et al, 2018;Nel & Baard, 2019 ;Khlifi, 2021;Nagarajah & Alagathurai, 2021;Hussein & Nounou, 2021 Hussein, 2017;Ahmed et al, 2017;Khlifi, 2021;Sarifudeen, 2021 (Hashim et al,2014;Mohamed & Basuony, 2015;Yassin, 2017;Hussein, 2017;qasim & al barghouthi, 2017;Abdi et al, 2018;Nel & Baard, 2019;Hussein & Nounou, 2021 (Singh., 2013;Pozniak, 2013;Dyczkowska, 2014;Mendes-Da-Silva et al, 2014;Fuertes-Callen et (Garg & Gakhar,2010;Kolsi ,2012;Abdi et al,2018) .…”
Section: ‫دفعت‬ ‫كما‬mentioning
confidence: 99%